Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 2 - Real Numbers - 2.2 - Addition and Subtraction of Rational Numbers - Problem Set 2.2 - Page 58: 92



Work Step by Step

We first apply the distributive property. Then, we simplify the resultant expression: $-\frac{3}{8}n-n-\frac{3}{14}n$ =$n(-\frac{3}{8}-1-\frac{3}{14})$ =$n(\frac{-3(7)-1(56)-3(4)}{56})$ =$n(\frac{-21-56-12}{56})$ =$n(\frac{-21-68}{56})$ =$n(\frac{-89}{56})$ =$-\frac{89}{56}n$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.